Hooked on a feeling Remembering sensory experience to unveil the world in Marcel Proust's Swann's Way (1913) and Günter Grass’ The Tin Drum (1959) - Boulman, Ciara (Trinity College (Dublin, Ireland). School of Languages, Literature and Cultural Studies, 2022)
This dissertation analyses the structure of the memory narrative in Swann’s Way by Marcel Proust and The Tin Drum by Günter Grass, through the lens of Edmund Husserl’s phenomenology as presented in Ideas I and II. More specifically, the author argues that the use of the child narrative in these two novels exemplifies many of Husserl’s concepts, starting with the individual experience of the world being founded in bodily experiences, being themselves the key to understanding it objectively. The extremely intimate perception of the child in both novels is based on sensory memory, allowing to recount more vividly complex memories such as family members and past events. Despite the obvious first-person narration at work however, both narratives are shown to be based on a plural narrative voice. The narrators distance themselves from their younger selves in order to adopt a more objective point of view of their past, and better communicate to the reader personal feelings. This search for objectivity also leads them to include a multitude of external points of view, without the initial memory being distorted as any added information is pointed out as being so. Swann’s Way and The Tin Drum initiate, in that sense, a reflection on how research on human matters (historical and socio-historical) should be told. The child narrative finally enables the exploration of the different layers of reality, ultimately inviting the reader to exercise their critical mind in order to escape the natural standpoint – a position in which one is entrapped in their subjective perception of the world-about-them.
Keywords: Comparative Literature